Principles for increasing equity in WASH research: understanding barriers faced by LMIC WASH researchers - J'Anna-Mare Lue; Salamata Bah; Kaelah Grant; Justine Lee; Leila Nzekele; James B. Tidwell (BMJ Global Health)
Introduction There have long been critiques of colonial legacies influencing global health. With growing public awareness of unjust systems in recent years, a new wave of calls for antiracist and decolonisation initiatives has emerged within the sector. This study examined research inequities in the water, sanitation and hygiene (WASH) sector, centring the perspectives of researchers from low-income and middle-income countries (LMICs), to identify barriers faced by WASH researchers in order to support more equitable changes in this subsector of global health.Methods Nineteen semistructured interviews were conducted with researchers of different backgrounds regarding nationality, gender and research experience. Researchers from eight countries were asked about their experiences and direct observations of discrimination across various stages of the research process. Five interviews were conducted with key WASH research funders to assess perceptions of obstacles faced by LMIC researchers, successes achieved and challenges faced by these organisations when working towards more equitable research processes within the WASH sector.Results The results were analysed using an emergent framework that categorised experiences based on power differentials and abuse of power; structural barriers due to organisational policies; institutional and individual indifference; othering speech, action and practices; and context-specific discrimination. The social-ecological model was combined with this framework to identify the types of actors and the level of co-ordination needed to address these issues. Researchers who worked in both LMICs and high-income countries at different career stages were particularly aware of discrimination. Ensuring pro-equity authorship and funding practices were identified as two significant actions to catalyse change within the sector.Conclusion Sector-wide efforts must centre LMIC voices when identifying research questions, conducting research, and in dissemination. Individuals, organisations and the entire WASH sector must examine how they participate in upholding inequitable systems of power to begin to dismantle the system through the intentional yielding of power and resources.